2017
DOI: 10.3329/ptcb.v27i2.35026
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency In vitro Regeneration of Gynura procumbens (Lour.) Merr.

Abstract: An efficient rapid in vitro regeneration protocol was described from nodal segment, leaf and petiole explants. MS medium supplemented with 1.0 mg/l BAP and 0.5 mg/l IAA was found best for the multiple shoot formation from nodal segments. In this combination 99% explants produced multiple shoots and the average number of shoots per explants was 20.1 ± 1.96. For petiole and leaf explants best response was observed on MS supplemented with 2.0 mg/l BAP, 1 mg/l IAA and 0.5 mg/l Kn. Petiole explants produced highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…But the mean of shoots from the callus of leaf explants was found to be 15.1 (Table 3) in this media combination (Fig 2k). Similar findings were also reported by Banu et al (2017) using leaf explants in Gynura. When the callus was cultured on MS+1.0 mg/l BAP + 0.5 mg/l Kn + 0.5 mg/l NAA multiple shoots were formed with the mean number of shoots 23.7 and 5.5 (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…But the mean of shoots from the callus of leaf explants was found to be 15.1 (Table 3) in this media combination (Fig 2k). Similar findings were also reported by Banu et al (2017) using leaf explants in Gynura. When the callus was cultured on MS+1.0 mg/l BAP + 0.5 mg/l Kn + 0.5 mg/l NAA multiple shoots were formed with the mean number of shoots 23.7 and 5.5 (Fig.…”
Section: Resultssupporting
confidence: 91%
“…2b) in this media (2.0 mg/l BAP and 0.5 mg/l NAA). Banu et al (2017) reported that combinations of BAP and NAA showed better results from node explants in Gynura. Ghimire et al (2010) also reported that BAP and NAA showed best response towards regeneration using petiole and leaf explants in Withania.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, leaf with petiole explants showed best shoot initiation when the calluses were transferred on MS medium supplemented with 1 mg/l BAP. Banu et al (2017) also observed better response in Gynura procumbens on MS with BAP, Kn and IAA supplemented medium. Khan et al (2018) also reported that combination of 2.0 mg/l BAP, 0.5 mg/l IAA and 0.02 mg/l NAA was best for the multiple shoot formation from nodal segments in Rauvolfia serpentina.…”
Section: Resultsmentioning
confidence: 67%
“…(Verma and Singh, 2007;Singh et al, 2011) also reported similar findings. Banu et al (2017) also observed better response in Gynura procumbens on MS with BAP and Kn supplemented medium. Combinations of MS with 2.0 mg/l BAP and 0.2 mg/l NAA also showed good response for multiple shoot formation using hypocotyl as explants (Table I).…”
Section: Resultsmentioning
confidence: 68%